Objective Truth and Contentiousness in Criminal Procedure: Confrontation and Mutual Addition - E. M. Ryabkov (Сибирское юридическое обозрение)
The article deals with one of the disputable issues of the modern theory of criminal court proceedings - truth as the aim of proof. The proposals on legislation improvement in this sphere are analyzed.